Molecular phylogeny of the Achatinoidea (Mollusca: Gastropoda) - Fontanilla, Ian Kendrich C.; Naggs, Fred; Wade, Christopher M. (Elsevier, 2017)
This study presents a multi-gene phylogenetic analysis of the Achatinoidea and provides an initial basis for a taxonomic re-evaluation of family level groups within the superfamily. A total of 5028 nucleotides from the nuclear rRNA, actin and histone 3 genes and the 1st and 2nd codon positions of the mitochondrial cytochrome c oxidase subunit I gene were sequenced from 24 species, representing six currently recognised families. Results from maximum likelihood, neighbour joining, maximum parsimony and Bayesian inference trees revealed that, of currently recognised families, only the Achatinidae are monophyletic. For the Ferussaciidae, Ferussacia folliculus fell separately to Cecilioides gokweanus and formed a sister taxon to the rest of the Achatinoidea. For the Coeliaxidae, Coeliaxis blandii and Pyrgina umbilicata did not group together. The Subulinidae was not resolved, with some subulinids clustering with the Coeliaxidae and Thyrophorellidae. Three subfamilies currently included within the Subulinidae based on current taxonomy likewise did not form monophyletic groups.